ANALISIS TEMA, AMANAT, DAN NILAI MORAL DALAM NOVEL "JANJI" KARYA TERE LIYE - Inayatul Amilah; Eli Syarifah Aeni; Woro Wuryani (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
A novel is composed of internal elements that are composed of themes and messages. Novels have a moral value that is beneficial to the reader. Since Tere Liye's novel Janji is a best-selling novel containing stories of people's life experiences, researchers are interested in analyzing the novel. The purpose of this study is to explain the themes, messages and moral values ​​of Tere Liye's novel "Janji". The research methods used are descriptive and qualitative. The data source for the analysis is Tere Liye's novel "Janji". After research, I found that Tere Liye's novel Janji has two kinds of her themes, the main her theme about promises and the sub-her theme about life's struggles. The novel Junji's message is an implicit message about mutual cooperation and an explicit message about the power of belief. The moral values ​​contained in Janji's novels include her four dimensions: relationship with self, relationship with others, relationship with nature, and relationship with God.